Medullary infarction of bilateral tibia - A rare presentation of tuberculosis: A case report with review of literature - Arpita Mishra; Ashok Singh; Ritesh K Agrawal; Om P Mishra (Wolters Kluwer Medknow Publications, 2023)
Background: Bony infarction or osteonecrosis is a rare, painful condition, reported in the setting of trauma, chronic steroid exposure, radiation, malignancies, and sickle cell anemia, diagnosed radiologically by its characteristic features in magnetic resonance imaging (MRI). The present case highlights the challenges in the diagnosis and management of an adolescent boy, who presented with medullary infarction of bilateral tibia. Clinical Description: A 15-year-old boy presented with severe pain in bilateral lower limbs, restricting his ability to stand and walk independently. There were no signs of inflammation or restriction of movements at the joints of the lower limb. Routine investigations were largely normal. The MRI of left tibia showed bone infarct in the middle shaft. Further investigations for the known causes of bone infarct were noncontributory. Considering a remote possibility that tuberculous endarteritis may cause such an infarct, tuberculin test was done which was positive. The chest X-ray was normal. Management and Outcome: Therapeutic trial of antitubercular drugs (2HRZE+10HRE) was given. The child showed a significant improvement in leg pain by 2 weeks of the start of therapy. On follow-up, he demonstrated complete resolution of the disease in X-ray and MRI. Conclusion: Tuberculosis endarteritis leading to bony infarction is an extremely rare phenomenon but biologically plausible. By reporting this case, we would like to convey that clinicians may consider bone infarct as a rare cause of unexplained, incapacitating limb pain in children, which, in the absence of known contributory factors, may be due to tuberculosis.